1999
DOI: 10.1046/j.1472-4642.1999.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in conservation areas of South Africa and its potential impact on floristic composition: a first assessment

Abstract: Summary Projected climate change has been suspected of affecting the biota of conserved nature areas in different and significant ways. Nevertheless, strategic management within some nature conservation agencies appears relatively unprepared for the possible consequences of climate change. National level planning of reserve design networks has also tended to skirt the issue, possibly owing to insufficient analysis. This paper provides a first assessment of the possible effects of climate change on plant divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…Hobbs, 1992;Simberloff et al, 1992;Beier and Noss, 1998) remains unresolved, at least in the sense that there appears to be no design appropriate for all components of a regional biota (Lindenmayer and Nix, 1993;Laurance and Laurance, 1999). Certainly, it is unlikely that the many thousands of CFR plant species that are dispersed short distances by ants (Bond, 1983) will be capable of migrating sufficiently fast to avoid the impacts of anthropogenic climate change (Rutherford et al, 2000;Midgley et al, 2003;see also van Dorp et al, 1997). Also of concern is the location of the upland-lowland and macroclimatic gradients.…”
Section: Planning For Persistencementioning
confidence: 99%
“…Hobbs, 1992;Simberloff et al, 1992;Beier and Noss, 1998) remains unresolved, at least in the sense that there appears to be no design appropriate for all components of a regional biota (Lindenmayer and Nix, 1993;Laurance and Laurance, 1999). Certainly, it is unlikely that the many thousands of CFR plant species that are dispersed short distances by ants (Bond, 1983) will be capable of migrating sufficiently fast to avoid the impacts of anthropogenic climate change (Rutherford et al, 2000;Midgley et al, 2003;see also van Dorp et al, 1997). Also of concern is the location of the upland-lowland and macroclimatic gradients.…”
Section: Planning For Persistencementioning
confidence: 99%
“…Several studies from elsewhere in the world may provide a model for such analysis (e.g. Rutherford et al 1999;Burns et al 2003). The Threatened Species Scientific Committee, set up under the Act, concluded that 'along with the issues of emissions reduction, the adaptation requirements of species and communities likely to be affected by climate change should be given greater priority' (http://www.deh.gov.au/biodiversity/ threatened/ktp/greenhouse.html).…”
Section: Recommendations For Data Collection and Analysismentioning
confidence: 99%
“…Further rapid climate change is likely to cause the extinction of many of the range-restricted and habitat-specialist members of the actively speciating flocks in the CFR (44)(45)(46)(47). However, by changing habitat characteristics and promoting population isolation, climate change may also enhance turnover of actively diversifying lineages.…”
Section: Rapid Diversification In the Cfrmentioning
confidence: 99%
“…The representation of biodiversity pattern (species, habitats, etc.) is only one component of an effective conservation plan; an explicit consideration of the evolutionary processes that will maintain biodiversity in the long term is also required (11,12), especially in a world that is increasingly threatened by habitat loss and climate change (44,45).…”
Section: Systematic Conservation Planningmentioning
confidence: 99%